Relevansi dan Kedalaman Pembelajaran Al-Qur’an Hadits di SMA: Analisis Pengembangan Materi Berbasis Deep Learning dalam Kerangka Kurikulum Merdeka - Muhammad Ryja Baihaqi; Syifa Fajriyah; Halimah; Devita Hendriyanti; Abdul Fadhil (Yayasan Al-Afif, 2025)
This study explores the relevance and depth of Qur’an and Hadith learning at the senior high school (SMA) level through the development of instructional materials grounded in a Deep Learning approach within the Merdeka Curriculum framework. The discussion emphasizes how Qur’an and Hadith materials can be structured not merely to prioritize rote memorization, but to promote contextual comprehension, critical reflection, and the internalization of spiritual as well as moral values among learners. Employing a qualitative library research design, this article analyzes curriculum documents, scholarly journals, and educational policy references related to Islamic education and deep learning pedagogy. The findings reveal that the Deep Learning approach strengthens the linkage between Qur’anic and prophetic teachings and adolescents’ real-life experiences, while simultaneously supporting the achievement of learning outcomes across attitudinal, cognitive, and skills domains. Moreover, the application of relevance, consistency, and sufficiency principles in material development contributes to more meaningful, dialogical, and applicable learning processes. The study concludes that implementing Deep Learning in Qur’an and Hadith instruction at the SMA level holds significant potential to enhance character building, critical thinking, and students’ spiritual awareness in addressing the challenges of the digital era and contemporary social change.